The Relationship between State Ownership and Tax Avoidance Level: Empirical Evidence from Vietnamese Firms - Ha, Nguyen Tran Thai; Quyen, Phan Gia (Journal of Asian Business Strategy, 2017)
This paper investigates the relationship between tax avoidance behavior and state-ownership level at corporates in Vietnam to find out whether state-ownership influence the tax avoidance behavior of Vietnamese firms. Effective tax rate presents for the tax avoidance level, in which higher effective tax rate means the lower tax avoidance level. In this research, the authors check robustness by using different methods to calculate the level of tax avoidance of corporates. Using Feasible Generalized Least Squares (FGLS) method with data of 460 enterprises listed on Vietnam Stock Exchange market from 2009 to 2015, the empirical result shows that the level of state ownership has an inverse relationship with tax avoidance behavior of corporates. In other words, the higher level of state-owned is, the fewer taxes they avoid. Empirical evidence also confirms that low concentration (≤ 30%) of state ownership has a positive effect on tax avoidance behavior. Besides that, size, firm performance, tangible assets level, and debt ratio have a meaningful positive relationship with the degree of tax avoidance, similarly prior studies.